Rise of blockchain and its synergy with AI/ML in transforming financial services - Praveen, R V S; Vemuri, Hari Krishna; Peri, Satya Subramanya Sai Ram Gopal; Sista, Sriharsha; Saxena, Vinay; Saxena, Parul (The International tax journal, 2025)
The rapid evolution of blockchain technology, alongside the growing sophistication of artificial intelligence (AI) and machine learning (ML), is reshaping the global financial services landscape. While blockchain ensures data immutability, transparency, and decentralized trust, AI/ML adds layers of predictive intelligence, automation, and real-time decision-making capabilities. Together, these technologies are driving innovations in fraud detection, smart contracts, decentralized finance (DeFi), Know Your Customer (KYC) compliance, and credit risk modeling. This paper explores how the synergy between blockchain and AI/ML is creating a new paradigm of secure, intelligent, and decentralized financial services. It also examines current applications, technological challenges, regulatory considerations, and future opportunities. Through a multi-disciplinary approach, the paper underscores the transformative potential of integrating blockchain and AI/ML to enable more resilient, inclusive, and efficient financial systems.